The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences